4D.07: ENDOTHELIN A RECEPTOR BLOCKADE REDUCES VASCULAR CALCIFICATION IN RATS WITH CHRONIC KIDNEY DISEASE AND MINERAL DISORDERS. (June 2015) - Agharazii, M.; Gauthier-Bastien, A.; Ung, R.V.; Mac-Way, F.; Richard, D.; Lariviere, R.
Abstract : Objective: Increased risk of cardiovascular disease in patients with chronic kidney disease (CKD) has been related to vascular stiffness and isolated systolic hypertension as a result of vascular calcification due to mineral metabolism abnormalities. Using a rat model of CKD with vascular calcification, we found a marked increase in endothelin-1 (ET-1) production in the media of calcified vessels suggesting a role for ET-1. This study was designed to investigate the effect of the ETA receptor antagonist atrasentan on vascular calcification and hemodynamic parameters in CKD rats with mineral metabolism abnormalities. Design and method: CKD was induced in Wistar rats by renal mass ablation and mineral metabolism abnormalities by a calcium/phosphate-rich diet and vitamin D supplementation (Ca/P/VitD) that lead to vascular calcification. A group of CKD rats given Ca/P/VitD was treated with the ETA receptor antagonist atrasentan (10 mg/kg/day) for 6 weeks. Hemodynamic parameters were determined by vessels catheterisation in anesthetised animals and the thoracic aorta was harvested for the assessment of calcification. Results: Treatment of CKD + Ca/P/VitD rats with the ETA antagonist atrasentan significantly reduced systolic blood pressure (109 ± 12 vs. 156 ± 8 mmHg, p < 0.05), pulse pressure (23 ± 3 vs. 60 ± 9 mmHg, p < 0.05) and carotid-femoral pulse wave velocity (481 ± 43 vs. 690 ± 28 cm/s, p < 0.01). These hemodynamic effects of ETA receptor blockade were associated with reduced vascular calcification assessed both by Micro-CT scanning (0.12 ± 0.03 vs. 0.24 ± 0.04 AU, p < 0.05) and von Kossa staining (1.9 ± 1.1 vs. 10.6 ± 2.5 AU, p < 0.05). Conclusions: Our study shows for the first time that ETA receptor blockade reduces vascular calcification and the associated hemodynamic abnormalities in this model of CKD-related vascular calcification.